2015
DOI: 10.1101/033340
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Phylogenetic and functional substrate specificity for endolithic microbial communities in hyper-arid environments

Abstract: Under extreme water deficit, endolithic (inside rock) microbial ecosystems are considered environmental refuges for life in cold and hot deserts, yet their diversity and functional adaptations remain vastly unexplored. The metagenomic analyses of the communities from two rock substrates, calcite and ignimbrite, revealed that they were dominated by Cyanobacteria, Actinobacteria, and Chloroflexi. The relative distribution of major phyla was significantly different between the two substrates and biodiversity esti… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(25 citation statements)
references
References 33 publications
(55 reference statements)
2
23
0
Order By: Relevance
“…3) but so far we cannot ascertain a factor that would drive the observed separation beyond the fact that it is not substrate type. While it would be of interest to compare our communities to other endolithic communities, such as those studied by Chacón et al (2006), Crits-Christoph et al (2016), Horath and Bachofen (2009) and De la Torre et al (2003), this is not technically possible given that all of those studies used alternative methods for commu-nity analyses (Clone libraries, DGGE, metagenomes) that do not allow direct comparisons.…”
Section: The Endolithic Microbial Communitiesmentioning
confidence: 99%
“…3) but so far we cannot ascertain a factor that would drive the observed separation beyond the fact that it is not substrate type. While it would be of interest to compare our communities to other endolithic communities, such as those studied by Chacón et al (2006), Crits-Christoph et al (2016), Horath and Bachofen (2009) and De la Torre et al (2003), this is not technically possible given that all of those studies used alternative methods for commu-nity analyses (Clone libraries, DGGE, metagenomes) that do not allow direct comparisons.…”
Section: The Endolithic Microbial Communitiesmentioning
confidence: 99%
“…This work provides a new insight into the behavior of cyanobacteria in endolithic communities under extreme solar radiation, as happens in the hyper-arid core of the Atacama Desert. Despite the sole development of lithobiontic microbial communities in endolithic habitats in different lithic substrates in this desert (39,(55)(56)(57) which act as a first line of defense against the damage provoked by high light exposure, the presence of second and third lines of cyanobacterial defense (39,40,42) points to the existence of specific, not previously characterized, adaptations to the harmful effects of high PAR and UVR, too.…”
Section: Discussionmentioning
confidence: 90%
“…Although Chroococcidiopsis is the dominant cyanobacterium in endolithic habitats in hot deserts, such as the Atacama (Dong et al, 2007;Crits-Christoph et al, 2016;Meslier et al, 2018;Ertekin et al, 2020;Qu et al, 2020;Casero et al, 2021), Negev (Israel) and Namib (southern Africa) Deserts (Qu et al, 2020), other coccoid taxa have also been found in endolithic assemblages from the Atacama Desert, such as Gloeocapsa (Crits-Christoph et al, 2016;Ertekin et al, 2020.;Casero et al, 2021) and Halothece (Ertekin et al, 2020). Recent culture-dependent and culture-independent studies, also in the Atacama Desert, have shown the occurrence of Synechococcus, Gloeocapsopsis (Casero et al, 2021), Aliterella, and Pleurocapsa minor (Jung et al, 2019).…”
Section: Discussionmentioning
confidence: 99%